51 An observational study evaluating the improvement in performance of inpatient gastroenterology services following the implementation of a transformation plan. (3rd November 2019) - Pathak, Suraj; Verma, Ajay
Abstract : Introduction: The incumbent arrangements were on Deene C Ward (DCW), 29 patients under the care of three Consultants doing twice weekly ward rounds (WR) not prospectively covered, newly admitted and unwell patients reviewed by any WR as a safety net arrangement. This was transformed to a Digestive Diseases Unit (DDU), bed base reduced from 29 beds (3 side rooms, 3 x 6 bedded bays, a 5 bedded bay, & a 3 bedded bay), to 20 beds, by reducing 6 bedded bays to 4 beds, and converting the 3 bedded bay to a nurse-led Gastroenterology Treatment Area (GTA) for day-case ambulatory patients. This facilitated the introduction of a Consultant of the Week (CotW) model. The CotW, for 2 weeks (prospectively covered), is responsible for daily DDU WRs of all 20 patients under their care, review of in-patient (IP) referrals, in-reach into urgent care wards, and support of GTA. There is minimal outpatient (OP) commitment. Outcomes were analysed at 12 months to assess the impact on patient care. Methods: A retrospective observational study was conducted to benchmark and evaluate changes in consultant led care. Statistical analysis was performed using Microsoft Excel. Conclusion: The reconfiguration of Gastroenterology IP services has been a great success. A reduction in bed base (which many at management level were reticent about) has facilitated a CotW model of care to be implemented. The IP service is now SAFER compliant. Length of stay has significantly reduced by 26.2%. Weekly discharges per bed, and Consultant reviews, has significantly increased by 34.2% & 84.1% respectively. In addition, GTA treats >90 patients per month, generating income, preventing admissions, facilitating earlier discharges, and freeing capacity in the main hospital ambulatory unit. This reconfiguration shows that a CotW model of care is optimal, successful, and SAFER compliant, even if a bed base reduction is required to facilitate this.